Few-layer graphene shells and nonmagnetic encapsulates: A versatile and nontoxic carbon nanomaterial - Bachmatiuk, Alicja; Mendes, Rafael G.; Hirsch, Cordula; Jaehne, Carsten; Lohe, Martin R.; Grothe, Julia; Kaskel, Stefan; Fu, Lei; Klingeler, Ruediger; Eckert, Juergen; Wick, Peter; Ruemmeli, Mark H. (ACS nano, 2013)
In this work a simple and scalable approach to coat nonmagnetic nanoparticles with few-layer graphene is presented. In addition, the easy processing of such nanoparticles to remove their core, leaving only the 3D graphene nanoshell, is demonstrated. The samples are comprehensively characterized, as are their versatility in terms of functionalization and as a material for electrochemical storage. Indeed, these 3D graphene nanostructures are easily functionalized much as is found with carbon nanotubes and planar graphene. Electrochemical investigations indicate these nanostructures are promising for stable long-life battery applications. Finally, initial toxicological investigations suggest no acute health risk from these 3D graphene nanostructures. © 2013 American Chemical Society.
CRIS-Team Scopus Importer:2023-03-20
Keywords: cyclic voltammetry studies; graphene nanostructures; graphene-coated oxide nanoparticles; toxicity tests